Sistem Informasi Penjualan Berbasis Web di Toko Buku Raja Murah - Sigit Sugiyanto (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2011)
With the website, the Raja Murah Bookstores provide information on-line and will enable customers quickly, accurately and efficiently to get the information. In this site visitors can view the company profile, products offered and available are also facilities for the admin to update the data in the website. The analytical method used is the method of directional data flow from the analysis, the required input and output systems. Among other product data, categories, polls and news articles insert. In making this website, use PHP scripts and MySQL database. conducted inter-system design are: create DFD (Data Flow Diagram), database settings, and user interface. Analysis of performance tested on the login process and data entry on the form